Grade migration and important prognostic factors in a pathology specimen for radical radiotherapy in prostate cancer patients - Majewski, Wojciech; Lange, Dariusz; Stanek-Widera, Agata; Itrych, Bartosz; Krzysztofiak, Tomasz; Jarząb, Michał; Oczko-Wojciechowska, Małgorzata; Kajor, Maciej; Tarnawski, Rafał (Polish Journal of Pathology, 2022)
The study aimed to evaluate grade migration and prognosis depending on pathologic features in patients with prostate cancer treated with radical external beam radiotherapy. The study included 139 patients with an initial Gleason score of 7 (3+4 or 4+3) i.e., Grade Group 2-3 (GG2-GG3) treated between 2008 and 2013. The clinical outcome was assessed with respect to biochemical control (BC) and biochemical disease-free survival (bDFS). After re-evaluation, the majority of patients (96 patients – 69%) were up-graded from GG2-3. Finally, there were 4 patients (3%) with grade GG1, 12 patients (9%) – GG2, 27 patients (19%) – GG3, 51 patients (37%) – GG4 and 45 patients (32%) – GG5. In 42 patients (30%) a cribriform pattern was observed. Among the analyzed factors only the GGs were important for BC (p = 0.011) and the cribriform pattern was of borderline significance (p = 0.06). The 5-year biochemical control was 100% in GG1-3 and 84% in GG4-5. The 5-year biochemical control was 81% and 93%, if cribriform or no cribriform pattern was detected, respectively. In conclusion, re-evaluation and verification of pathology specimens in accordance with contemporary rules upgraded the Gleason score in the majority of patients. The aggressive behavior of prostate cancer starts to occur from GG 4. Cribriform pattern almost tripled the biochemical failure rate.